Analysis of the Impact of the Covid-19 Pandemic and PSBB Policy on MSMEs in Pasar Baru Karawang, Nagaasari Village - Muhammad Fahrul Adly; Dadan kurniansyah; Kariena Febriantin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The global COVID-19 pandemic has had an impact on various sectors, especially the economic sector. This economic impact is not only felt globally but also domestically. In Indonesia, this of course also has a significant impact, such as in the tourism sector, trade sector, industry including Micro, Small and Medium Enterprises (UMKM). Not a few companies have suffered losses due to being affected by this pandemic, which has an impact on the laying off of employees and even termination of employment. The Central Government in order to overcome the Covid-19 Pandemic in March 2020 issued PP Number 21 of 2020 concerning Large-Scale Social Restrictions(PSBB) with the aim of limiting the movement of people and goods and requiring the public if there is no urgent need to stay at home. This will of course have an impact on the limited number of MSME actors with fewer consumers who shop directly compared to normal days, especially for MSME actors around the Tuparev area, Pasar Baru Karawang, and around the Karawang Square Area.